PATTERN OF STROKE IN TYPE 2 DIABETIC SUBJECTS VERSUS NON DIABETIC SUBJECTS - Zafar, Azra; Shahid, Syed Khurram; Siddiqui, Maimoona; Khan, Farrukh Shohab (Journal of Ayub Medical College Abbottabad, 2007)
Background: Diabetes mellitus is a well-recognized risk factor for ischaemic stroke. Stroke in diabetic patients is different from stroke in non-diabetics from several perspectives. There is no local study on this topic. This is the first study from Pakistan, in which pattern of stroke in diabetics have been described and compared with non-diabetics. The object of this study was to compare pattern of stroke in diabetic subjects with non-diabetics. Methods: This is a prospective comparative cross sectional study, carried out at Liaquat national hospital, Karachi, neurology department from October to March 2006. Fifty patients were enrolled in diabetic group and 50 in non-diabetic. Clinical features, risk factors and stroke patterns were identified. Results: Mean age was 59.5 (±11.82) in diabetics and 60.4 (±14.8) in non diabetics. There was slight preponderance of male patients in non diabetic group. Out of 50 diabetic patients, 44 (88.0%) had ischaemic stroke and 6 (12.0%) had intracerebral haemorrhage. In non-diabetics, 29 (58.0%) had ischaemic stroke while 21 (42.0%) had intracerebral haemorrhage. On further analysis of ischaemic stroke, cortical infarcts (CI) was found in 22, sub cortical infarcts (SCI) in 14, brainstem in 5 and cerebellar in 2 diabetic patients. CI was also the commonest subtype of ischaemic stroke in nondiabetics. Conclusion: Patterns of stroke in diabetics are different from non-diabetics. Ischaemic stroke is more prevalent than hemorrhagic stroke in diabetics. Sub cortical infarcts are more common in diabetics than non diabetics (p=0.04). Keywords: Stroke, diabetes mellitus, stroke pattern